Gut microbiota CLA and IL-35 induction in macrophages through Gαq/11-mediated STAT1/4 pathway: an animal-based study - Xiaomin Su; Yazheng Yang; Yunhuan Gao; Juanjuan Wang; Yang Hao; Yuan Zhang; Rongcun Yang (Gut Microbes)
Gut microbiota/metabolites not only participate in the food and energy metabolism but also contribute to the host immune response and homeostasis. The alternation of gut microbiota/metabolites has been widely related to intestinal and extra-intestinal disorders such as intestinal bowel diseases (IBDs). Bactericidal substances from gut epithelial cells can regulate the composition of gut microbiota. However, the effects of regenerating protein 4 (REG4) (human)/(Reg4) (mice), a potentially bactericidal substance from gut epithelial cells, on the gut immune homeostasis maintain elusive. Here, we found that REG4/Reg4 is essential in maintaining gut immune homeostasis through REG4/Reg4 associated gut microbiota. Reg4 knockout (KO) mice were highly sensitive to DSS-mediated colitis, whereas human REG4 intestine epithelial cell transgenic (huREG4IECtg) mice exhibited more resistance to DSS-mediated colitis. Mechanistically, sequencing of gut microbiota and liquid chromatography-mass spectrometry showed that REG4/Reg4 could affect the composition of gut microbiota. REG4/Reg4 associated gut microbiota such as Lactobacillus could metabolize linoleic acid (LA) into conjugated linoleic acid (CLA). Immunoprecipitation and immunoblot showed that CLA could effectively promote the expression of IL-35 in macrophages through Gαq/11 mediated activation STAT1/4. Thus, our results demonstrate that REG4/Reg4 plays a critical role in maintaining gut immune homeostasis through CLA-mediated IL-35+ macrophages.